Dual‐Mission Management in Social Entrepreneurship: Qualitative Evidence from Social Firms in the United Kingdom. (2nd September 2014) - Costanzo, Laura A.; Vurro, Clodia; Foster, Doug; Servato, Flavio; Perrini, Francesco; Karatas‐Ozkan, Mine; Anderson, Alistair R.; Fayolle, Alain; Howells, Jeremy; Condor, Roland
<x xml:space="preserve">Abstract</x> Social enterprises are at risk of undermining the authenticity of their social purpose in the attempt to manage and balance multiple stakeholders' expectations. This study explores dynamics of dual‐mission management in relation to a group of U.K. social enterprises via an inductive qualitative multicases method. Results suggest that approaches to dual‐mission management vary along a continuum, ranging from the dimension of high compartmentalization to the dimension of high integration. It emerged that blended strategic planning, tailored production processes, and blended governance and management structures are critical key drivers of integration approaches to dual‐mission management.